2019
DOI: 10.1126/scitranslmed.aar5012
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic cell-penetrating activity propels Omomyc from proof of concept to viable anti-MYC therapy

Abstract: Inhibiting MYC has long been considered unfeasible, although its key role in human cancers makes it a desirable target for therapeutic intervention. One reason for its perceived undruggability was the fear of catastrophic side effects in normal tissues. However, we previously designed a dominant-negative form of MYC called Omomyc and used its conditional transgenic expression to inhibit MYC function both in vitro and in vivo. MYC inhibition by Omomyc exerted a potent therapeutic impact in various mouse models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
211
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(237 citation statements)
references
References 66 publications
14
211
1
Order By: Relevance
“…Myc has been shown to be involved in multiple aspects of tumorigenesis, [39] both at the intracellular and extracellular level, being responsible for cell division, increased cell metabolism, immune tolerance, and survival to treatment of tumor cells. Omomyc has been instrumental in demonstrating this therapeutic opportunity, first as a transgene [20] and more recently as a therapeutic polypeptide, [40] while also demonstrating the complete safety of the approach for normal tissues. Omomyc has been instrumental in demonstrating this therapeutic opportunity, first as a transgene [20] and more recently as a therapeutic polypeptide, [40] while also demonstrating the complete safety of the approach for normal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Myc has been shown to be involved in multiple aspects of tumorigenesis, [39] both at the intracellular and extracellular level, being responsible for cell division, increased cell metabolism, immune tolerance, and survival to treatment of tumor cells. Omomyc has been instrumental in demonstrating this therapeutic opportunity, first as a transgene [20] and more recently as a therapeutic polypeptide, [40] while also demonstrating the complete safety of the approach for normal tissues. Omomyc has been instrumental in demonstrating this therapeutic opportunity, first as a transgene [20] and more recently as a therapeutic polypeptide, [40] while also demonstrating the complete safety of the approach for normal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, increased MYC expression has previously been shown to exert oncogenic effects that depend on a sharp threshold of MYC expression, reminiscent of the effects we observe for PIK3CA activation ( 51 ). As the first specific pharmacological inhibitor of MYC was recently reported ( 52 ), its use in the PIK3CA H1047R hPSC system may provide additional insight into the potential role of MYC as a molecular link between oncogenic PI3Kα activation, NODAL expression and stemness.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Omomyc homodimers were found to be more thermodynamically stable than MAX homodimers, and equivalent to Omomyc/MYC and Omomyc/MAX heterodimers [79], in contrast to some of the previously published data reported in Section 2.1 [13,52]. In the presence of DNA, thermal denaturation and fluorescence anisotropy experiments showed that both homodimeric Omomyc and heterodimeric Omomyc/MAX, but not heterodimeric Omomyc/MYC, bind canonical E-boxes at physiological temperature [79], confirming Omomyc's originally described mechanism of action and in line with the EMSA results at 37 ºC shown in [52]. The basic region of Omomyc homodimers was also shown to assume the same contacts to DNA as MYC/MAX heterodimers [13], confirming the capacity of Omomyc to compete with MYC for binding to DNA.…”
Section: Recombinant Omomyc Is a Cell-penetrating Peptidementioning
confidence: 98%
“…The observation that other bHLHLZ proteins could behave as protein transduction domains [77], together with the fact that Omomyc contains an amphipathic helical basic region [52]-a common feature of cell-penetrating peptides [78]-encouraged us to test if the purified Omomyc mini-protein itself could be used as a therapeutic agent. To do so, Omomyc was recombinantly produced in E. coli, purified, characterized and tested for its cell-penetrating capacity and therapeutic efficacy against NSCLC models in vitro and in vivo [79]. Circular dichroism and nuclear magnetic resonance assays revealed that recombinant Omomyc forms homodimers and heterodimers with MYC and MAX, as for its transgenic counterpart.…”
Section: Recombinant Omomyc Is a Cell-penetrating Peptidementioning
confidence: 99%